DIABETIC KETOACIDOSIS IN A NEW ONSET ELDERLY TYPE 1 DIABETES AFTER SARS-CoV-2 VACCINATION: ASSOCIATION OR COINCIDENCE? - Raman, Muhamad Fazrin; Kim, Serena Khoo Sert; Ching , Tee Hwee (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION In the era of the COVID-19 pandemic, several cases of new onset diabetes associated with COVID-19 have been reoprted. Additionally, patients with diabetes, a high-risk population, are prioritised for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccination. The vaccine against the (SARS-CoV-2) could represent a new environmental trigger for autoimmune disorders such as Graves’ disease, immune thrombotic thrombocytopenia, autoimmune liver diseases, Guillain-Barré syndrome, systemic lupus erythematosus and type 1 diabetes. CASE We report a case of diabetic ketoacidosis in a new onset Type 1 diabetes in an elderly lady following SARS-CoV-2 vaccination. A 69-year-old female with a history of treated TB abdomen in 2015 with no history of diabetes received her second dose of SARS-CoV-2 vaccination (COMIRNATY) on 21st August 2021. Two weeks following vaccination, she developed osmotic symptoms, reduce appetite and lethargy. Her random blood glucose (RBS) was 41 mmol/L, serum ketone 4.4 mmol/L, pH of 7.29 mmHg, bicarbonate 12.5 mmol/L and serum osmolarity of 298 mOsm/kg. She was treated for DKA with intravenous insulin infusion and hydration with resolution of DKA within 12 hours. Anti-Glutamic Acid Decarboxylase and anti-Islet Cells antibodies were positive with low fasting C-peptide of 102 pmol/L. She was discharged well with basal bolus insulin. 4 months later Hba1c reduced from 15.6% to 7.7% with a random C-peptide of 152 pmol/L. CONCLUSION The occurrence of hyperglycaemia crisis following SARS-CoV-2 vaccine in patients with pre-existing diabetes is known but the occurrence of new onset autoimmune diabetes following vaccination is rare. Further studies are needed to better understand the underlying pathogenesis of autoimmune diabetes following SARS-CoV-2 vaccine.